2016
DOI: 10.1039/c6py00441e
|View full text |Cite
|
Sign up to set email alerts
|

Boron difluoride formazanate copolymers with 9,9-di-n-hexylfluorene prepared by copper-catalyzed alkyne–azide cycloaddition chemistry

Abstract: The synthesis and characterization of copolymers based on boron difluoride formazanate (BF2L) and 9,9-di-n-hexylfluorene (hex2Fl) units are described. A series of model compounds [(BF2L)- were not dependant on copolymer molecular weight. However, the title copolymers may show promise as a light-harvesting material based on their thin-film optical band gap of 1.67 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…Photoluminescence tuning in dependence on MW has been investigated by scholars [51][52][53]. It was found that the length of the polymer chain plays an important role in the solid-state emission.…”
Section: Resultsmentioning
confidence: 99%
“…Photoluminescence tuning in dependence on MW has been investigated by scholars [51][52][53]. It was found that the length of the polymer chain plays an important role in the solid-state emission.…”
Section: Resultsmentioning
confidence: 99%
“…For example, CuAAC chemistry was used to produce polymer 68 (Chart 4), which gave rise to l max = 557 nm (e = 25 700 M À1 cm À1 ) and l PL = 696 nm (F PL = 1%) in DMF. 86 Polymer 68 also exhibited a reversible wave associated with its electrochemical reduction to its poly(radical anion) form (E red1 = À0.73 V vs. Fc 0/+ ). Thorough examination of the properties of 68 compared to model compounds constructed from various combinations of the building blocks of the polymer later revealed that p-electron conjugation involving the BF 2 formazanate units did not extend beyond the triazole rings formed during polymerization.…”
Section: Group 12 (Zn)mentioning
confidence: 99%
“…Thereafter, by employing this Cu(PPh 3 ) 3 Br catalyst, various functions of topologic polytriazoles have been reported . Among them, the development of efficient solid‐state luminescent polymers is critically important for application in the areas of fluorescent chemosensors and organic light‐emitting diodes, etc .…”
Section: Metal‐catalyzed Click Polymerizationmentioning
confidence: 99%